2014
DOI: 10.1017/s2045796014000201
|View full text |Cite
|
Sign up to set email alerts
|

Does the Strengths and Difficulties Questionnaire – self report yield invariant measurements across different nations? Data from the International Child Mental Health Study Group

Abstract: Due to the lack of a common acceptable model across all countries, namely the same numbers of factors (i.e., dimensional invariance), it was not possible to perform the metric and scalar invariance test, what indicates that the SDQ self-report models tested lack appropriate measurement invariance across adolescents from these seven nations and it needs to be revised for cross-country comparisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 50 publications
6
72
0
1
Order By: Relevance
“…Given that no previous psychometric evaluation of the SDQ has taken place in South Africa, the current study therefore aimed to: (i) examine the means, standard deviation, distribution and internal consistency of the SDQ-S in a representative sample of adolescent boys and girls; (ii) compare gender differences in the above psychometric properties; (iii) determine the proportion of boys and girls who scored in the 'normal', 'borderline' and 'abnormal range' of SDQ-S subscales based on UK norms, and, if required, to generate South African cut-off scores; (iv) compare mean SDQ-S scores of the South African sample to previously reported normative data for SDQ-S scores in UK, Australian and Chinese samples; and (v) determine whether the South African SDQ-S data would fit the five-factor structure of the original UK SDQ-S. We hypothesised that significant differences on the basis of gender will exist in SDQ-S scores as found in previous studies (Becker et al 2015;Kremer et al 2015), hypothesised that South African cut-off scores may be required, as reported in other studies from LMICs (Kashala et al 2005;Menon et al 2007;Bakare et al 2010;Cortina et al 2013), and that there would be only partial support for the five-factor structure, as reported elsewhere (Rønning et al 2004;Richter et al 2011;Stevanovic et al 2014). We did not hypothesise any specific patterns of similarities or differences between the South African, UK, Australian and Chinese data, but were keen to explore the crosscountry potential of the instrument.…”
Section: Introductionmentioning
confidence: 83%
“…Given that no previous psychometric evaluation of the SDQ has taken place in South Africa, the current study therefore aimed to: (i) examine the means, standard deviation, distribution and internal consistency of the SDQ-S in a representative sample of adolescent boys and girls; (ii) compare gender differences in the above psychometric properties; (iii) determine the proportion of boys and girls who scored in the 'normal', 'borderline' and 'abnormal range' of SDQ-S subscales based on UK norms, and, if required, to generate South African cut-off scores; (iv) compare mean SDQ-S scores of the South African sample to previously reported normative data for SDQ-S scores in UK, Australian and Chinese samples; and (v) determine whether the South African SDQ-S data would fit the five-factor structure of the original UK SDQ-S. We hypothesised that significant differences on the basis of gender will exist in SDQ-S scores as found in previous studies (Becker et al 2015;Kremer et al 2015), hypothesised that South African cut-off scores may be required, as reported in other studies from LMICs (Kashala et al 2005;Menon et al 2007;Bakare et al 2010;Cortina et al 2013), and that there would be only partial support for the five-factor structure, as reported elsewhere (Rønning et al 2004;Richter et al 2011;Stevanovic et al 2014). We did not hypothesise any specific patterns of similarities or differences between the South African, UK, Australian and Chinese data, but were keen to explore the crosscountry potential of the instrument.…”
Section: Introductionmentioning
confidence: 83%
“…Nonetheless, the review of the literature shows that there are few studies of measurement invariance in the self-reported version of the SDQ [19,11,27,26,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Essau et al [38], with a sample of 2418 adolescents, found that the factorial structure of the SDQ differed across five European countries (Cyprus, England, Sweden, Germany, and Italy). Another important study, conducted by Stevanovic et al [39], did not find an acceptable model in countries from Europe, Asia, and Africa (India, Nigeria, Turkey, Croatia, Indonesia, Bulgaria, and Serbia). As so, they were not able to test for MI across countries.…”
mentioning
confidence: 98%
See 2 more Smart Citations